Aktivitas Antibakteri Ekstrak Etanol Daun Kapas (Gossypium barbadense L.) terhadap Staphylococcus epidermidis dan Propionibacterium acnes - khumaidi, akhmad; Nugrahani, Arsa Wahyu; Gunawan, Febriani (Jurnal Farmasi Udayana; Vol. 9, No. 1, Tahun 2020, 2020)
Gossypium barbadense L. is one of the plants that has the potential to be developed into an antibacterial agent. This study aims to determine the antibacterial ability of chemical compounds in ethanol extract of Gossypium barbadense L. leaves to Staphylococcus epidermidis and Propionibacterium acnes bacteria which are characterized by the formation of inhibitory zones. Extraction of Gossypium barbadense L. leaves was carried out by maceration using 96% ethanol. Antibacterial activity testing was carried out by agar diffusion method with a cylinder plate technique and the extract was made a concentration series. TLC bioautography and chromogenic reagents are used in the identification of groups of compounds that have antibacterial activity. The results showed that the ethanol extract of Gossypium barbadense L.  leaves gave the greatest inhibition at 70%  extract concentration ie 11.40 ± 0.32 mm against Propionibacterium acnes and 50% extract concentration against Staphylococcus epidermidis bacteria which was 12.28 ± 0.63 mm. The group of compounds that are thought to be responsible for antibacterial activity are flavonoids. Keywords: Antibacterial, Gossypium barbadense L. Leaves, Propionibacterium acnes, Staphylococcus epidermidis